Study on identification, assay and organoleptic quality of veterinary medicines in Ethiopia (Taylor & Francis Group, 2022)
Background Medicines of poor quality are currently prevailing problems undermining the quality of health care services in veterinary and human medicine. In this study, physico-chemical quality of veterinary medicines was evaluated. Methods A total of 959 veterinary medicines samples were collected during routine regulatory activities, i.e. pre-registration, re-registration, consignment checking and post-marketing surveillance, in Ethiopia. The samples were transported to Animal Products, Veterinary Drug and Feed Quality Assessment Centre (APVD-FQAC), which is the quality control laboratory of the Veterinary Drug and Feed Administration and Control Authority (VDFACA) and stored until analysis. The samples were subjected to visual inspection and chemical analysis following the United States, European or British Pharmacopoeias, or manufacturer's methods. Results The findings revealed that 12 (1.3%) of tested products showed defects in physical characteristics, packaging, or labelling information, while a total of 66 (6.9%) samples of the investigated products failed to comply with the Pharmacopoeias and supplier's specification limit set for assay. Of these, 60 samples did not comply with the minimum assay specification limit. Conclusion Overall, 8.2% of the investigated veterinary medicine samples did not comply with the specification set for the investigated quality attributes and thus were categorized as of poor quality. This indicates the need for continued strengthening of regulatory functions.